2010
DOI: 10.1007/s11666-010-9480-5
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Wear Behavior of Conventional and Nanostructured Plasma-Sprayed WC-Co Coatings

Abstract: WC-12%Co coatings were deposited by atmospheric plasma spraying using conventional and nanostructured powders and two secondary plasmogenous gases (He and H 2 ). Coating microstructure and phase composition were characterized using scanning electron microscopy (SEM), transmission electron microscopy (TEM), and x-ray diffraction techniques (XRD) techniques. This study examined wear and friction properties of the coatings under dry friction conditions. SEM was used to analyze abraded surface microstructure. Coat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 23 publications
1
30
0
1
Order By: Relevance
“…During spraying of WC-Co powders, significant changes in the chemical and phase compositions can occur [1]. The past two decades have seen extensive research in optimizing the feedstock powder characteristics, process parameters and post-treatments of wear-resistant hardmetal coatings [2][3][4][5][6][7][8][9][10][11][12][13][14]. Most research, however, has related to the coatings sprayed from agglomerated and sintered powders, with the typical particle size ranging from 10 to 50 lm and WC grain size ranging from 0.8 to 3.5 lm [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…During spraying of WC-Co powders, significant changes in the chemical and phase compositions can occur [1]. The past two decades have seen extensive research in optimizing the feedstock powder characteristics, process parameters and post-treatments of wear-resistant hardmetal coatings [2][3][4][5][6][7][8][9][10][11][12][13][14]. Most research, however, has related to the coatings sprayed from agglomerated and sintered powders, with the typical particle size ranging from 10 to 50 lm and WC grain size ranging from 0.8 to 3.5 lm [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Most research, however, has related to the coatings sprayed from agglomerated and sintered powders, with the typical particle size ranging from 10 to 50 lm and WC grain size ranging from 0.8 to 3.5 lm [2][3][4][5][6][7]. Optimization of these coatings has resulted in coating microstructures with negligible porosity, high fracture toughness and minimization of secondary carbide phases [2][3][4][5][6][7][8][9][10][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tribomechanical properties such as hardness, wear resistance, and strength are influenced primarily by the size and distribution of WC grains, the porosity, the volume fraction and thermo-mechanical properties of the metal matrix, and post-treatments of the composite hardmetal coating [1][2][3][4][5][6][14][15][16][17][18][19][20][21][22]. Both room temperature and higher temperature investigations have been conducted [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…For various thermal spray techniques, numerous studies emphasized the enhanced wear resistance of WC reinforced coatings against sliding wear [1], abrasive wear RESEARCH [2] as well as erosion [3] and erosion-corrosion [4]. For high velocity oxy fuel [5,6], plasma [7,8] and suspension flame [9] sprayed coatings, several authors investigated the tribological characteristics of stressed surfaces by employing different tungsten carbide grain-sized feedstocks. It was found that a decreased carbide grain size possesses a higher resistance against abrasion, sliding, or erosive wear.…”
Section: Introductionmentioning
confidence: 99%